TREATMENT OF NEGLEGTED STERNOCLAVICULAR (SC) DISLOCATION WITH CANNULATED SCREW AND CERCLAGE WIRE OSTEOSYNTHESIS - Azharuddin Azharuddin (Universitas Syiah Kuala, 2014)
Abstrak. Dilaporkan sebuah kasus seorang laki-laki 18 tahun, mengalami kecelakaan lalu lintas terjatuh dari tabrakan sepeda motor 6 bulan sebelum datang berobat ke poliklinik Orthopaedi RSUZA Banda Aceh, pasien mengeluh nyeri bahu kiri. Dari pemeriksaan fisik didapatkan pada inspeksi terlihat hilangnya kontur normal pada sisi kiri sternum dan ada tonjolan ujung bagian dalam tulang klavikula kiri. Pemeriksaan sistem vaskular dan saraf tungkai atas kiri dalam batas normal. Pada pemeriksaan ronsen dada posisi postero-anterior didapatkan dislokasi Sternoklavicula kiri dengan pergeseran sekitar 5 cm. Kami lakukan operasi elektif, reduksi terbuka dengan immobilisasi dan fusi menggunakan canulated screw dan kawat cerclage. Didapatkan hasil operasi yang memuaskan baik dari aspek anatomis dan fungsinya pada evaluasi 1 tahun. Abstract. Reported a 18-year-old man road motor cycle accident. He presented to the policlinic orthopaedic department at dr. Zainoel Abidin General hospital with left shoulder pain. He was diagnosed with a left anterior SC dislocation neglegted. On physical examination, the patient loss of the normal anatomical contour with prominent of the left medial clavicle into the superior mediastinum was noted. A vascular examination was normal, with intact radial, ulnar, median, and axillary nerve sensation and function. Review of the chest postero anterior view revealed a dislocation of the medial clavicle with displacement of the medial clavicular fragment anterior to the manubrium. We treated with open reduction and internal fixation using cannulated screwing and cerclage osteosynthesis with favourable outcome up to one year follow up.